2016
DOI: 10.1186/s12913-016-1520-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of healthy ageing: public health policy targets

Abstract: BackgroundThe public health policy agenda oriented towards healthy ageing becomes the highest priority for the European countries. The article discusses the healthy ageing concept and its possible determinants with an aim to identify behavioral patterns related to healthy ageing in selected European countries.MethodsThe healthy ageing is assessed based on a composite indicator of self-assessed health, functional capabilities and life meaningfulness. The logistic regression models are used to assess the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 59 publications
5
107
0
3
Order By: Relevance
“…In general, both of these models showed a geographic pattern similar to that of the AHA-B model in earlier studies, in which the highest scores are observed in northern countries and western Europe, but with great variability in the order of countries listed [ 64 ]. Results reported by Perales et al and Sowa et al follow a similar geographic gradient [ 58 , 65 ]. Measuring mental well-being with a subjective variable, "satisfaction with life", affected the distribution of AHA by country.…”
Section: Discussionsupporting
confidence: 69%
“…In general, both of these models showed a geographic pattern similar to that of the AHA-B model in earlier studies, in which the highest scores are observed in northern countries and western Europe, but with great variability in the order of countries listed [ 64 ]. Results reported by Perales et al and Sowa et al follow a similar geographic gradient [ 58 , 65 ]. Measuring mental well-being with a subjective variable, "satisfaction with life", affected the distribution of AHA by country.…”
Section: Discussionsupporting
confidence: 69%
“…In order to understand the physiological brain aging process, longitudinal aging studies are superior to single point studies since they provide a good indication of when the first cognitive deficits occurred during lifetime [41,42]. The special characteristic of our study is that we used a single cohort of NMRI mice to examine the effects of the physiological aging…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in the past about the concept of healthy aging focused on the standpoint of the elderly [9][10][11][12][13][14][15]. Furthermore, aging perspectives are increasingly associated with actual experiences in adulthood [16].…”
Section: Introductionmentioning
confidence: 99%